2021
DOI: 10.55563/clinexprheumatol/egnd1i
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the age at diagnosis in the disease expression of primary Sjögren syndrome. Analysis of 12,753 patients from the Sjögren Big Data Consortium

Abstract: Objective. To analyse how the main components of the disease phenotype (sicca symptoms, diagnostic tests, immunological markers and systemic disease) can be driven by the age at diagnosis of primary Sjögren's syndrome (pSS). Methods. By January 2021, the participant centres had included 12,753 patients from 25 countries that fulfilled the 2002/2016 classification criteria for pSS. The age at diagnosis was defined as the time when the attending physician confirmed fulfilment of the criteria. Patients were clust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 26 publications
(30 reference statements)
4
27
0
Order By: Relevance
“…Our data showed that EopSS was more commonly associated with ILD, and the prevalence of ILD tended to increase with increase of onset age. This result is consistent with findings of a previous international study, which included 12,753 pSS patients from 25 countries and showed that the frequency of pulmonary involvement tended to increase with increase of age at disease diagnosis (27). Two recent studies suggested that aging and male sex were risk factors for pSS-ILD (22,28).…”
Section: Differences In Clinical Manifestationssupporting
confidence: 92%
“…Our data showed that EopSS was more commonly associated with ILD, and the prevalence of ILD tended to increase with increase of onset age. This result is consistent with findings of a previous international study, which included 12,753 pSS patients from 25 countries and showed that the frequency of pulmonary involvement tended to increase with increase of age at disease diagnosis (27). Two recent studies suggested that aging and male sex were risk factors for pSS-ILD (22,28).…”
Section: Differences In Clinical Manifestationssupporting
confidence: 92%
“…Our findings also suggest that patients with older age, lower unstimulated salivary flow rate at baseline and more prominent inflammation in the salivary glands were more likely to have a poor response to dental treatment assessed by the stimulated salivary flow at D90, a measure of glandular function (46). Corroborating with these findings, it was recently described in the large population of the Sjögren Big Data Consortium registry study that the frequency of altered objective oral tests, including unstimulated salivary flow rate, progressively increases with older ages at diagnosis (53). It was also recently described by Berman et al that focus score >1 was associated with the number of caries, emphasizing the importance of the degree of inflammation in the salivary glands as a determinant of impaired oral status in pSS (9).…”
Section: Discussionmentioning
confidence: 85%
“…Moreover, the exacerbated regulation of interferon-α (INF-α) coding genes in the peripheral blood and salivary gland cells stimulates the B-cell activating factor (BAFF) production, a TNF family ligand that stimulates the maturation and differentiation of B lymphocytes (1,4). The most frequent pSS symptoms are xerophthalmia and xerostomia: ≅ 92% and 93% at presentation, respectively (5). Hyposalivation has important consequences for the oral health (6).…”
Section: Introductionmentioning
confidence: 99%
“…nary, peripheral nervous system (PNS) and central nervous system (CNS) domains (4). This severe systemic expression contrasts strongly with the lower frequency of autoantibodies in comparison with women (5).…”
Section: Defining the Appropriate Epidemiological Scenario (Table I)mentioning
confidence: 99%
“…The wide phenotypic variation in the presentation of primary SS is strongly linked with the age at diagnosis, since the frequency of the main features (glandular, extraglandular and immunological) are modulated by age. There is a progressive increase in the frequency of dry mouth and pulmonary involvement at diagnosis with age (2.2% increase per each 10 years), and a progressive decrease in the frequency of lymphadenopathy, glandular involvement, and the positive rate of anti-Ro/La antibodies and immunological markers (4). Therefore, it is important to know that the phenotype at presentation of Sjögren's will be very different in a 10-year-old child than in an 80-yearold person.…”
Section: Pearl Consider Age At Diagnosis a Key Driver Of How The Dise...mentioning
confidence: 99%